Biofeedback as a form of neurorehabilitation in Parkinson’s disease - Iłżecka, Joanna (Journal of Education, Health and Sport, 2021)
Parkinson’s disease is a degenerative disease of the nervous system. An important element in the treatment of the disease is neurorehabilitation. One of the forms of neurorehabilitation may be biofeedback. The above technique uses electronic devices that allows an individual to learn how to change the body’s function in order to reduce the clinical symptoms of the disease and improve health. Previous studies have confirmed that biofeedback has a beneficial effect on the health of patients with Parkinson’s disease. The aim of the work was a review of the literature on biofeedback as a form of neurorehabilitation in this disease.